Development of low-cost chicken based longganisa - Macaraig, Jean Ann S.; Dumelod, Benelyn Domingo (2001., 2001)
Experimental results show that the incorporation of texturized soy protein or TSP is an effective way to reduce the cost of production of chicken longganisa. Since it has no fat and its protein content is comparable with that of chicken meat, it is a good meat extender, which maintains the protein level while keeping the fat content low. Statistical analysis using Analysis of Variance (α=0.05) showed that the three formulations use in the study- salty, sweet, and sweet and spicy- were significantly different from one another, the last being the most acceptable with an over-all acceptability score of 7.93,corresponding to like very much. for the determination of the acceptable level of TSP (0,40 and 50% in relation to the amount of chicken meat), results showed that there was no significant difference but the most acceptable was the one with 40% TSP. The standardized product was determined to be: like moderately, moderately dark brown for its outer appearance, light brown for its inner part, with moderate longganisa aroma, moderately tender, moderately juicy, slightly spicy, and in terms of saltiness and sweetness, midway between bland and very salty/sweet. The suggested market price for the product is P151.00 per kilogram with a mark up of 25% over its production cost of P123.05 per kilogram. It is higher than that of the existing pork longganisa which is sold in the market at P110.00 per kilogram since chicken leg quarters yield only 50% meat. However, the cost may be significantly reduced with the use of imported mechanically recovered poultry meat (MRPM). The price of TSP-substituted chicken longganisa may be higher than pork longganisa, but its reduced fart and high protein content and the absence of nitrites are just some of the advantages of the product. Therefore, with the advantages of the product, good advertisement, and consumer education, the chicken longganisa formulation in this study could be a big hit, not only in the Philippines but in the Asian market as well.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Poultry processing; Sausage